Thermal stability, mechanical and optical properties of novel addition cured PDMS composites with nano-silica sol and MQ silicone resin. (29th September 2015) - Chen, Dongzhi; Chen, Fengxiang; Hu, Xiaoyun; Zhang, Hongwei; Yin, Xianze; Zhou, Yingshan
Abstract: A series of novel addition cured polydimethylsiloxane (PDMS) composites with a given weight amount of nano-silica sol were prepared using MQ silicone resin as reinforcing agent by hydrosilylation for the first time. Influences of the used amount of MQ silicone resin on morphology, thermal stability, mechanical and optical properties of these novel PDMS composites were mainly studied. It was found that thermal stabilities and transparencies of the novel PDMS composites with a given amount of nano-silica sol decreased with an increment in weight fraction of MQ silicone resin, as compared with that of PDMS composites without MQ silicone resin (SMQ-0), which were likely ascribed to an increasing amount of remained silanols and the increasing size of aggregated particles in PDMS composites, respectively. However, mechanical properties of the novel PDMS composites with a given weight of nano-silica sol were improved significantly with amount of MQ silicone resin increasing, especially their elongations at break, which were up to 10 times. This was a great breakthrough for PDMS composites. The prominent improvements in mechanical properties were probably attributed to strong interaction of PDMS chains and uniformly dispersed particles resulted from crosslink of MQ silicone resin and nano-silca sol. This strategy for preparing novel addition curing PDMS composites provides a guide method to develop high elastic PDMS composites with desirable properties in industry applications.